Effects of menthol application on the skin during prolonged immersion in swimmers and controls - Botonis, P. G.; Geladas, N. D.; Kounalakis, S. N.; Cherouveim, E. D.; Koskolou, M. D. (Scandinavian Journal of Medicine & Science in Sports, 2016)
We hypothesized that menthol application on the skin would enhance vasoconstriction of subjects immersed in cool water, which would reduce heat loss and rectal temperature (Tre) cooling rate. Furthermore, it was hypothesized that this effect would be greater in individuals acclimatized to immersion in 24 °C water, such as swimmers. Seven swimmers (SW) and seven physical education students (CON) cycled at 60% VO2 max until Tre attained 38 °C, and were then immediately immersed in stirred water maintained at 24 °C on two occasions: without (NM) and with (M; 4.6 g per 100 mL of water) whole-body skin application of menthol cream. Heart rate, Tre, proximal-distal skin temperature gradient, oxygen uptake (VO2), electromyographic activity (EMG), and thermal sensation were measured. Tre reduction was similar among SW and CON in NM and CON in M (-0.71±0.31 °C in average), while it was smaller for SW in M (-0.37±0.18 °C, P < 0.01). VO2 and heart rate were greater in M compared with NM condition (P = 0.01). SW in M exhibited a shift of the threshold for shivering, as reflected in increased VO2 and EMG activity, toward a higher Tre compared with the other trials. Menthol application on the skin before immersion reduces heat loss, but defends Tre decline more effectively in swimmers than in non-swimmers.